Respuesta :

[tex] \qquad \qquad \huge \rm \huge \overbrace{\underbrace{ \color{red}{ Answєr}}}[/tex]

hєrє wє gσ ~

[tex] \qquad⧉ \sf \: \: {x}^{2} - 5x + 6 = 0[/tex]

[tex] \qquad⧉ \sf \: \: {x}^{2} - 3x - 2x+ 6 = 0[/tex]

[tex] \qquad⧉ \sf \: \: {x}^{} (x - 3) - 2(x - 3) = 0[/tex]

[tex] \qquad⧉ \sf \: \: {}^{} (x - 3) (x - 2) = 0[/tex]

nσw, wє gσt twσ cαѕєѕ :

#1. whєn (х - 3) = 0

[tex]\qquad \sf  \dashrightarrow \: x = 3[/tex]

αnd

#2. whєn (х - 2) = 0

[tex]\qquad \sf  \dashrightarrow \: x = 2[/tex]

ACCESS MORE